A Novel Oxy‐Oxonia(Azonia)‐Cope Reaction: Serendipitous Discovery and Its Application to the Synthesis of Macrocyclic Musks. Issue 10 (October 2014) - Zou, Yue; Zhou, Lijun; Ding, Changming; Wang, Quanrui; Kraft, Philip; Goeke, Andreas
Abstract This brief review, including new experimental results, is the summary of a talk at the GDCh conference 'flavors & fragrances 2013' in Leipzig, Germany, 11th–13th September, 2013. Musk odorants are indispensable in perfumery to lend sensuality to fine fragrances, a nourishing effect to cosmetics, and a comforting feeling to laundry. We have recently found serendipitously a new oxy‐oxonia‐Cope rearrangement. In this account, we review the background of oxonia‐sigmatropic rearrangements and the discovery of this novel reaction. Special attention is focused on the versatile lactone and lactam formation reactions via [n+4] ring enlargement and the macrocyclization in the synthesis of new macrocyclic musks. The synthesized structures provide new insights into the structureodor relationships of musks.